(untitled) (International Journal of Food and Nutritional Sciences, 2022)
People are changing their mind towards organic food and beverages because of their health consciousness and their safety factor only. Organic food are cultivated without using the artificial fertilizers and synthetic chemicals. Some sought of organic foods and beverages are selling exclusively in organic shops, in super markets and other small scale units also. Brand preference is the most important factor in marketing field. Most of the people are consuming the products with brand addiction. So the impact of the study is to determine the brand preference towards organic food and beverages with an extra ordinary citation to Tirunelveli City.